Atrial fibrillation prevalence revisited. (7th August 2013) - Friberg, L.; Bergfeldt, L.
Abstract Background The estimate of 0.4–1.0% prevalence of atrial fibrillation in the most recent American guidelines is based mainly on studies including patients with permanent atrial fibrillation (AF), although recent evidence shows that the stroke risk is similar with paroxysmal and persistent AF. Our objective was to determine the prevalence of AF in Sweden, irrespective of type and to what extent patients with AF receive adequate stroke prophylaxis. Method Retrospective study of patients with a clinical diagnosis of atrial fibrillation between 2005 and 2010 in the national Swedish Patient Register matched with data from the National Prescribed Drugs Register. Results We identified 307 476 individuals with a diagnosis of atrial fibrillation. Of these, 209 141 were still alive on the last day of the inclusion period, signifying a prevalence of clinically diagnosed AF in Sweden of 2.9% of the total adult (≥20 years) population. Only 42% of them had purchased an oral anticoagulant within 6 months of the first presentation with AF during the study period. Those at the highest risk of stroke were those least likely to receive anticoagulant treatment. Undertreatment was common amongst women and individuals >80 years, whilst overtreatment was common amongst young men without risk factors. Conclusion The prevalence of atrial fibrillation is at least 2.9% of the Swedish adult population, not counting 'silent atrial fibrillation'. The official US figures probably underestimate the magnitude of the problem by a factor of 3–5. More than 80% had risk factors motivating anticoagulation therapy.